Alabama : the history of a Deep South state - Rogers, William Warren, 1929-2017 (University of Alabama Press, 1994)
"In 1934 Carl Carmer wrote that "Alabama felt a magic descending, spreading, long ago." That magic, whether long ago or in the recent past, continues to captivate and fascinate both citizens and observers from afar, and many historians have tried to capture its essence. Albert J. Pickett produced the first comprehensive history of the state in 1852, but no historian has matched his effort since A.B. Moore's 1934 work - at least not until now." "Alabama: The History of a Deep South State is divided into three sections, the first concluding with the South's defeat in 1865, the second ending with the beginning of the Jazz Age in 1920, and the third bringing the story into 1993." "In both chronological and topical organization, the book examines traditional subjects such as politics, military events, economics, and social movements. It discusses the roles of individual leaders, from politicians to creative artists. Both general readers and careful students of Alabama history will discover less well known people and issues treated in sections devoted to race, Indians, women, and the environment. Attention is given to health, education, organized labor, civil rights, and cultural elements - from literature to sports - that have affected the lives of Alabamians. There is strong emphasis upon the common people, those who have been rightly described as the "bone and sinew" of Alabama." "Each section of the book was written by a scholar with strong ties to Alabama who has devoted much of his or her professional life to the study of that period of the state's history. Although the three sections reflect individual style and interpretation, the authors have collaborated closely on overall themes and organization. The work relies on both primary sources and such important secondary works as monographs, articles, and unpublished theses and dissertations to provide fresh insights, new approaches, and new interpretations. The result is an objective look at a colorful, often